The design and validation of the enabling conditions for collective teacher efficacy scale (EC-CTES). Issue 2 (16th March 2020) - Donohoo, Jennifer; O'Leary, Tim; Hattie, John
Abstract : Purpose: High levels of collective teacher efficacy (CTE) within a school is known to be associated with improved student learning. CTE is a marker of the level of shared efficacy among teachers within a school. Knowledge of the levels of CTE within a school does not, though, support its development. To properly support school leaders in nurturing CTE, knowledge of the status of the enabling conditions for CTE within their schools is necessary to identify areas of strength and opportunities for improvement. Armed with such knowledge, school leaders can then begin the journey of cultivating CTE within their schools. Design/methodology/approach: Drawing upon previous research, contextual predictors of collective efficacy were identified and a questionnaire was created. Confirmatory factor analysis was used to evaluate the proposed factor structure. Necessary revisions were completed and in phase 2 of the field test, a new instrument was validated using factor analysis. Findings: The preliminary validation of the Enabling Conditions for Collective Efficacy Scale (EC-CTES) is presented in this paper. This study provides evidence in support of a factor model with five related first-order factors that describe the enabling conditions for CTE, which include: Empowered Teachers, Embedded Reflective Practices, Cohesive Teacher Knowledge, Goal Consensus, and Supportive Leadership. A conceptual framework for "Leading Collective Teacher Efficacy" is provided. Research limitations/implications: The identification and measurement of the malleable, contextual factors that contribute to the formation of CTE has been lacking in previous research. While most of the previous research focused on the remote sources of CTE, very few studies have examined the proximate sources. Correlations between some factors were high, in particular Empowered Teachers and Supportive Leadership. Although there is evidence these factors can be seen as making unique contributions, future work will focus on the inclusion of additional items to more clearly make the distinction between the factors. In addition, there were limitations based on the sample in this study and future research should focus on a broader sample of participants. Practical implications: While there are currently several CTE scales widely used in research, contextual factors that serve to enhance CTE in schools have not been captured in existing instruments. The identification of the contextual antecedents of CTE will be useful to system and school leaders because this information can be used to help inform their leadership practice as they work to help instill a greater sense of collective efficacy among the teaching faculty in their schools. Social implications: CTE is of great interest to system and school leaders because it predicts teachers' willingness to invest the time and energy required to attain educational goals and results in greater effort. The productive behavior on the part of the adults in schools characterized by high levels of CTE leads to improved student outcomes. Originality/value: This study detailed the design and validation of a teacher perception survey to capture information related to the dimensions associated with the enabling conditions of CTE.